Folate-decorated poly(3-hydroxybutyrate-co-3-hydroxyoctanoate) nanoparticles for targeting delivery: optimization and in vivo antitumor activity. (12th June 2016) - Zhang, Chan; Zhang, Zhuo; Zhao, Liangqi
Abstract: Context : Doxorubicin (DOX)-loaded folate-targeted poly(3-hydroxybutyrate-co-3-hydroxyoctanoate) [P(HB-HO)] nanoparticles [DOX/FA-PEG-P(HB-HO) NPs] have potential application in clinical treatments for cervical cancer due to specific affinity of folate and folate receptor in HeLa cells. Objective : The aim of this study was to develop an optimized formulation for DOX/FA-PEG-P(HB-HO) NPs, and investigate the targeting and efficacies of the nanoparticles. Materials and methods : DOX/FA-PEG-P(HB-HO) NPs were prepared by W1 /O/W2 solvent extraction/evaporation method, and an orthogonal experimental design [L9 (3 4 )] was applied to establish the optimum conditions. The physico–chemical characteristics, microscopic observation and in vivo antitumor study of the nanoparticles were evaluated. Results : The optimum formulation was obtained with DOX 10% (w/v), FA-PEG-P(HB-HO) 6.5% (w/v), PVA 3%(w/v) and oil phase/internal water phase volume ratio of 3/1. The size distribution, drug loading and encapsulation efficiency of the optimized nanoparticles were 150–350 nm, 29.6 ± 2.9% and 83.5 ± 5.7%, respectively. In vitro release study demonstrated that 80% of the drug could release from the nanoparticles within 11 days. Furthermore, in vitro microscopic observation and in vivo antitumor study showed that DOX/FA-PEG-P(HB-HO) NPs could inhibit HeLa cells effectively, and the tumor inhibition rate (TIR) in vivo was 76.91%. Discussion and conclusions : DOX/FA-PEG-P(HB-HO) NPs have been successfully developed and optimized. In vitro drug release study suggested a sustained release profile. Moreover, DOX/FA-PEG-P(HB-HO) NPs could effectively inhibit HeLa cells with satisfying targeting, and reduce side effects and toxicity to normal tissues. DOX/FA-PEG-P(HB-HO) NPs were superior in terms of inhibiting HeLa tumor over non-targeted formulations therapy.